2020
DOI: 10.3390/nu12030790
|View full text |Cite
|
Sign up to set email alerts
|

Human Milk Oligosaccharide Profile Variation Throughout Postpartum in Healthy Women in a Brazilian Cohort

Abstract: Human milk oligosaccharide (HMO) composition varies throughout lactation and can be influenced by maternal characteristics. This study describes HMO variation up to three months postpartum and explores the influences of maternal sociodemographic and anthropometric characteristics in a Brazilian prospective cohort. We followed 101 subjects from 28–35 gestational weeks (baseline) and throughout lactation at 2–8 (visit 1), 28–50 (visit 2) and 88–119 days postpartum (visit 3). Milk samples were collected at visits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
79
3
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 56 publications
(93 citation statements)
references
References 45 publications
8
79
3
3
Order By: Relevance
“…However, the participants from the STEPS Study did not have obesity (median BMI = 23.0, [ 14 ]), which may explain the observed discrepancy between these two studies. Consistent with our observations, a positive association between pre-pregnancy BMI and LNnT concentrations at 2–8 days and at 88–119 days postpartum was recently reported in a Brazilian cohort that included women with overweight and obesity [ 11 ], suggesting that the relationship between BMI and LNnT concentrations might change when higher BMIs are included in the analysis. LNnT consumption can promote positive health benefits to the infant gut [ 27 ] and therefore identifying maternal predictors of LNnT concentrations may prove useful in future attempts to develop interventions for optimizing HM composition and infant nutrition.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…However, the participants from the STEPS Study did not have obesity (median BMI = 23.0, [ 14 ]), which may explain the observed discrepancy between these two studies. Consistent with our observations, a positive association between pre-pregnancy BMI and LNnT concentrations at 2–8 days and at 88–119 days postpartum was recently reported in a Brazilian cohort that included women with overweight and obesity [ 11 ], suggesting that the relationship between BMI and LNnT concentrations might change when higher BMIs are included in the analysis. LNnT consumption can promote positive health benefits to the infant gut [ 27 ] and therefore identifying maternal predictors of LNnT concentrations may prove useful in future attempts to develop interventions for optimizing HM composition and infant nutrition.…”
Section: Discussionsupporting
confidence: 92%
“…Maternal genetics (expression patterns of Secretor (Se) and Lewis (Le) gene alleles, which code for different fucosyltransferases) have the greatest impact on HMO composition [ 26 ]. However, we and several others have concluded that various maternal characteristics (age, race, ethnicity, and parity) including pre-pregnancy BMI [ 10 , 11 , 17 ] and maternal glucose homeostasis [ 17 ] can affect HMO composition during lactation. To our knowledge, this study presented herein is one of the first to explore the relationship between maternal BMI and HMO composition in a large group of women whose BMIs encompassed Class I–Class III obesity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maternal reports indicated that 76.4% of infants received 7 or more human milk feedings per day, which falls within the recommended range of exclusive human milk feeding (29,30). HMO analysis revealed that 86.0% of mothers were classified as HMO secretors, which falls within the reported range of prior studies (i.e., 51.0%‐89.1%) (15,18,20,31). Characteristics of the mother‐infant pairs grouped by HMO secretor status at 1 month are described in Table 1.…”
Section: Resultssupporting
confidence: 84%
“…Obviously, the analysis of the absolute HMO content does not give detailed information about the change of individual HMOs with regard to different factors. To address such questions, a good number of studies have therefore focused on the quantification of the most important milk sugars [ 7 , 12 , 17 , 20 , 28 , 29 , 42 , 43 , 46 , 47 , 48 ]. These have for instance shown that 3FL increases up to almost threefold throughout the course of lactation regardless of the milk status and gestational age [ 7 , 12 , 17 , 28 , 29 , 32 , 43 , 47 , 48 ].…”
Section: Structure Of Human Milk Oligosaccharides and Human Milk Cmentioning
confidence: 99%